Domestic science in the public schools - Finlayson, Elizabeth (My University, 1904)
Introduction: Manual training originated in Europe many years ago. It was used first as a means of developing industrial skill. The men who secured this training were thus enabled to enter the factories and advance the manufacturing interests. Its importance in aiding the child to secure a better general education, better self-control and better intellectual development was at first entirely overlooked. Manual training was introduced into this country by certain broadminded men, who as practical educators, foresaw the advantage of such training. Under these men and their successors the European system has been modified and adapted to meet the needs of the American school, and educators feel that it is fulfilling a want and has become a permanent part of our public school system.
Citation: Finlayson, Elizabeth. Domestic science in the public schools. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Domestic Science; Manual Training; Education Curriculum; Schools; Theses; Manuscripts (documents)